An Application of DEA Method in Measuring Regional Efficiency in Serbia - Radonjić, Ljubivoje Gorica (Industrija, 2020)
The purpose of this article is to present a more detailed evaluation of Serbia’s spatial efficiency disparities by analyzing the effects of regional characteristics such as infrastructure, investment in new fixed assets, and level of employment. In that sense, data envelopment analysis (DEA) is applied to find efficient frontiers, which extends the application of the production function of the regions. This approach of mathematical programming optimization allows assessing the effectiveness of the regional spatial aspects analyzed. The DEA method is based on the inputs and outputs of used indicators and it evaluates how efficiently analyzed regions can transform their potentials into positive economic results. The identification of efficiency of the regions offers the opportunity to study regional disparities to evaluate a more detailed and reasonable implementation of regional policy in Serbia.